2021
DOI: 10.1055/s-0041-1731277
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Bilirubin Monitoring in Preterm Infants of 23 to 34 Weeks' Gestation

Abstract: Objective The study aimed to evaluate the validity of transcutaneous bilirubin (TcB) measurements at three sites in premature infants born at 230/7 to 346/7 weeks' gestational age (GA) compared with total serum bilirubin (TSB) measurements. Study Design A prospective study was conducted at Banner – University Medical Center Phoenix, where informed consent was obtained from the infant's parent or legally authorized representative. Cohort A was comprised of infants 230/7 to 286/7 weeks' GA and Cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
3
4
0
Order By: Relevance
“…Previously, only four studies evaluated this site in neonates. Unlike our study, all four studies were conducted on preterm infants [11,[17][18][19]. Although the correlation coefficient of the interscapular site (r = 0.86 and r = 0.85) was higher in two studies using JM-103 than that of our study, the correlation coefficient of the interscapular site (r = 0.846) calculated for only late preterm infants in the present study was similar to these studies [11,17].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Previously, only four studies evaluated this site in neonates. Unlike our study, all four studies were conducted on preterm infants [11,[17][18][19]. Although the correlation coefficient of the interscapular site (r = 0.86 and r = 0.85) was higher in two studies using JM-103 than that of our study, the correlation coefficient of the interscapular site (r = 0.846) calculated for only late preterm infants in the present study was similar to these studies [11,17].…”
Section: Discussionsupporting
confidence: 60%
“…Accordingly, the light transmitted by the transcutaneous bilirubinometer can easily access bilirubin and be reflected; thereby, levels are measured correctly [14]. Weber et al [18] reported that the most sensitive and specific area for TcB measurement was the interscapular site in infants born at 23 to 28 6/7 weeks of gestation and the sternum in infants born at 29 to 34 6/7 weeks of gestation. Similar to our study, Agrawal et al [11] measured TcB levels at the forehead, sternum, and interscapular site in preterm infants with a gestational age of ≤ 34 weeks, and the strongest correlation was at the interscapular site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interscapular was preferred site in neonates born at 23 to 34 weeks, sternal TCB was more sensitive and specific in babies born at 29 to 35 weeks. 18 In the present study, the average of the forehead and sternal value was a better predictor of neonatal hyperbilirubinemia. The area under the ROC curve for TCB measurements, TCB-AV, TCB -S and TCB-FH were 0.894, 0.887 and 0.878 respectively.…”
Section: Original Articlesupporting
confidence: 45%
“…12,15 Studies have compared various sites for TCB measurement in late preterm infants and the results are contradicting. 11,[16][17][18] Agrawal G et al studied the diagnostic accuracy of TCB at three different sites (Forehead, sternum, and interscapular area) in early preterm infants opined that the interscapular region as a reliable area to measure TCB in infants 34 weeks. 11 They reported a correlation coefficient of 0.82, 0.84 and 0.86 for the forehead, sternum,…”
Section: Discussionmentioning
confidence: 99%